The Effect of Independent Attitude and Motivation on Vocational School Students' Interest in Entrepreneurship - Rini, Agustina Mardika; Marsono, Marsono; Yoto, Yoto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine and analyze the influence of independent attitudes and motivation on the entrepreneurial interest of students majoring in Accounting and Finance at SMK Negeri 1 Boyolangu. This type of research is quantitative. The population in this study were 108 students majoring in Accounting and Finance at SMK Negeri 1 Boyolangu. The number of samples in this study amounted to 52 respondents using purposive sampling method. Hypothesis testing in this study using multiple regression analysis. The results showed that simultaneously, independent attitude and motivation had a significant effect on the entrepreneurial interest of students majoring in Accounting and Finance at SMK Negeri 1 Boyolangu. Partially, motivation has a positive and insignificant effect on interest in entrepreneurship and independent attitude has a positive and significant effect on interest in entrepreneurship.